Joyland [compact disc, unabridged] - King, Stephen, 1947- (Simon & Schuster Audio, 2013)
Set in a small town North Carolina amusement park in 1973, Joyland tells the story of the summer in which college student Devin Jones comes to work as a carny and confronts the legacy of a vicious murder, the fate of a dying child, and the ways both will change his life forever.